PENGARUH FAKTOR IKLIM DAN KEPADATAN PENDUDUK TERHADAP KEJADIAN DEMAM BERDARAH DENGUE DI KOTA ADMINISTRASI JAKARTA TAHUN 2018-2020 - Rafi Aflah Fadlirahman; Firda Alfianti; Alfitra Firizkia Luthfiana Dewi; Balqis Nila Estasya; Nur Indah Iriana; Diva Muthia Rahma; Silvia Khansa; Putri Rizki Amelia (Politeknik Kesehatan Kemenkes Bengkulu, 2022)
Problems: Dengue Hemorrhagic Fever (DHF) is a disease that is transmitted through the bite of the Aedes sp. and it is still a public health problem in Indonesia. The survival of the dengue mosquito and the spread of the disease can be affected by climate factors such as rainfall, humidity, and air temperature. Population density is also a risk factor for the spread of dengue fever. The Aim of The Research: The purpose of this study was to determine the relationship between climate factors and population density on the incidence of dengue fever in the Jakarta Administrative City in 2018-2020. Reseacrh Method: This study uses an ecological study design by conducting statistical correlation tests on climate factor data with dengue cases in the Jakarta Administration City in 2018-2020. Spatial analysis was conducted to see the relationship between population density and the incidence of DHF in the same location. The Result: The results of this study did not find a significant relationship between rainfall and air temperature with the incidence of DHF in the Jakarta Administration City in 2018-2020. Air humidity and the incidence of dengue fever showed a significant relationship in Central Jakarta, West Jakarta, and North Jakarta, p-values ​​were p=0.017, p=0.043, and p=0.034. Population density produces dengue-prone areas in the city of Jakarta and has a significant influence. Conclusion: It is necessary to understand about the risk of DHF especially in areas with dense population density and increase our knowledge how to prevent this desease